Procedural and Methodological Quality in Preclinical Stroke Research–A Cohort Analysis of the Rat MCAO Model Comparing Periods Before and After the Publication of STAIR/ARRIVE - Friedrich, Jacqueline; Lindauer, Ute; Höllig, Anke (Frontiers in Neurology, 2022)
The translation of preclinical stroke research into successful human clinical trials remains a challenging task. The first Stroke Therapy Academic Industry Roundtable (STAIR) recommendations for preclinical research and several other guidelines were published to address these challenges. Most guidelines recommend the use of physiological monitoring detect the occurrence of undesired pathologies such as subarachnoid hemorrhage and to limit the variability of the infarct volume and –therefore- homogenize the experimental result. From the years 2009 and 2019, 100 published articles each using a rat stroke model were analyzed to quantify parameters related to anesthesia, physiological monitoring, stroke model type, ischemia verification, and overall study quality over time. No significant difference in the frequency of cerebral blood flow (CBF) measurements over time (28/34% for 2009/2019) was found. Notably, significantly fewer studies reported temperature, blood pressure, and blood gas monitoring data in 2019 compared to 2009. On the other hand, an increase in general study quality parameters (e.g. randomization, reporting of approval) was seen. In conclusion, the frequency of periinterventional monitoring decreased over time. Some general methodological quality aspects, however, partially increased. CBF measurement – the gold standard for ischemia verification - was applied rarely. That said, both methodological and procedural quality still need to be improved.